The Cancer-Testis Long Non-coding RNA PCAT6 Facilitates the Malignant Phenotype of Ovarian Cancer by Sponging miR-143-3p - Tan, Xiaofang; Shao, Yang; Teng, Yue; Liu, Siyu; Li, Weijian; Xue, Lu; Cao, Yuepeng; Sun, Chongqi; Zhang, Jinhong; Han, Jing; Wu, Xiaoli; Xu, Hanzi; et al. (Frontiers in Cell and Developmental Biology, 2021)
Background: It has been reported that long non-coding RNAs (lncRNAs) play critical roles in tumorigenesis. However, their roles in ovarian cancer (OC) remain to be elucidated. The aim of this study was to uncover the function and underlying mechanisms of PCAT6 in OC. Methods: The expression pattern of PCAT6 in OC was analyzed in the GSE137238, GSE143897 and Gene Expression Profile Interactive Analysis (GEPIA) datasets. Kaplan–Meier Plotter online software was used for survival analysis. Loss-of-function assays and gain-of-function assays were used to assess the function of PCAT6 in OC development. Moreover, small-RNA sequencing, bioinformatic analysis, luciferase assays and rescue experiments were carried out to clarify the potential mechanism of PCAT6 in OC. Results: PCAT6 expression was significantly increased in OC tissues and positively correlated with advanced stages and with poor overall survival, progression-free survival and post-progression survival. Knockdown of PCAT6 in A2780 and SKOV3 cells inhibited OC cell proliferation, migration and invasion. In contrast, Overexpression of PCAT6 exerted the opposite effects on OC cells. Notably, PCAT6 bound to miR-143-3p and affected the expression of transforming growth factor (TGF)-β-activated kinase 1 (TAK1). Subsequent rescue assays confirmed that upregulation of miR-143-3p decreased the PCAT6 overexpression-induced promotion of proliferation, migration and invasion. Moreover, downregulation of miR-143-3p reversed the PCAT6 knockdown-induced inhibition of proliferation, migration, and invasion. Conclusions: Our findings demonstrate that PCAT6 plays an oncogenic role in OC and may be useful as a therapeutic target for OC.